TEKNOLOGI OZONISASI UNTUK MEMPERTAHANKAN KESEGARAN CABAI CULTIVAR KENCANA SELAMA PENYIMPANAN - Ali Asgar; d musaddad; Dondy A Setyabudi; Zahirotul H Hasan (Jurnal Penelitian Pascapanen Pertanian, 2015)
The study aimed to determine the effect of storage temperature and ozonered chillies freshness Kencana. The study was conducted from October-DeLembang. The study was conducted using a randomized block design with a smain plot which consists of: 1) 10° C and 2) ambient temperature. As a sub-without immersion, 2) control with immersion (0 ppm), 3) 0.5 ppm and 4) 1 pcolor, freshness, and appearance of red chili with treatment storage temperatreatment in terms of color, freshness and appearance and panelists preferred.